(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
The pilot study investigates adolescents’ information-seeking behavior for decision-making purposes. The aim of the study is to explore adolescents’ information-seeking behavior in everyday life decision-making situations. In this research we use a survey method with a questionnaire comprised of hypothetical decision-making situations which allows respondents to elaborate on their answers. The research aims to reveal whether adolescents engage in deliberate information seeking when facing everyday life decisions and if so, which information sources they use. Moreover, the research explores the importance attached by adolescents to information in making decisions. In addition, the results will be used for developing a methodology for a large-scale research project.